Hepatic traumatism: conservative non-surgical handling - Piñeyro, Alberto; Torterolo, Edgardo; Bergalli, Luis; Aizen, Bernardo (Cirugía del Uruguay, 1984)
The author presents a case of hepatic traumatism diagnosed by laparotomy and computed tomography in the course of a close abdominal traumatism. An analysis is made of the conditions under which it is possible to treat a subcapsular haematoma of the li• ver with a conservative non surgical procedure.